Archiwalia Włodzimierza Korsaka w zbiorach Wojewódzkiej i Miejskiej Biblioteki Publicznej im. C. Norwida w Zielonej Górze = Włodzimierz Korsak's archives in the collections of the C. Norwid Provincial and Municipal Public Library in Zielona Góra - Rećko, Janusz (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
In 1973, the management of WiMBP named after C. Norwid in Zielona Góra began efforts to obtain the archives of Włodzimierz Korsak. The purchased materials include primarily manuscripts (autographs dominate), typescripts, notes, sketches, correspondence, press clippings and personal documents (ID cards, certificates, forms, etc.). The legacy of W. Korsak is collected in 21 folders and contains 2,536 pages. The literary materials are supplemented by photographs (196 pieces) and a few drawings (14 pieces), as well as works and documents by his wife (Felicja Korsakowa), materials by other people and anonymous notes.
Keywords: Korsak, Włodzimierz (1886-1973); archiwa prywatne; zbiory biblioteczne; łowiectwo; myśliwi; private archives; library collections; hunters; hunting